Where Is Garlic Mustard? Understanding the Ecological Context for Invasions of Alliaria petiolata. (30th March 2022) - Rodgers, Vikki L; Scanga, Sara E; Kolozsvary, Mary Beth; Garneau, Danielle E; Kilgore, Jason S; Anderson, Laurel J; Hopfensperger, Kristine N; Aguilera, Anna G; Urban, Rebecca A; Juneau, Kevyn J
Abstract: The invasive plant Alliaria petiolata (garlic mustard) has spread throughout forest understory and edge communities in much of North America, but its persistence, density, and impacts have varied across sites and time. Surveying the literature since 2008, we evaluated both previously proposed and new mechanisms for garlic mustard's invasion success and note how they interact and vary across ecological contexts. We analyzed how and where garlic mustard has been studied and found a lack of multisite and longitudinal studies, as well as regions that may be under- or overstudied, leading to poor representation for understanding and predicting future invasion dynamics. Inconsistencies in how sampling units are scaled and defined can also hamper our understanding of invasive species. We present new conceptual models for garlic mustard invasion from a macrosystems perspective, emphasizing the importance of synergies and feedbacks among mechanisms across spatial and temporal scales to produce variable ecological contexts.